Management strategies for idiopathic urethritis. Issue 1 (February 2016) - Henderson, L.; Farrelly, P.; Dickson, A.P.; Goyal, A.
Summary: Introduction: Williams and Mikhael (1971) described idiopathic urethritis (IU) as a self-limiting condition that affects boys aged 5–15 years, with symptoms of urethrorrhagia, dysuria and haematuria. However, a proportion of boys will remain symptomatic for several years, and may develop urethral stricture (Poch et al., 2007; Palagiri et al., 2003). There is no universally effective treatment for IU, although various strategies have been employed. Objective: To review the presentation and long-term outcomes of boys with IU, and present the efficacy of management strategies that have been utilised. Study design: A retrospective review was performed of all boys with IU. It was based on clinical and cystoscopic findings for presentation, medical history, management and clinical progress. Results: Fifty-four boys were included, with a median age of 11 years (range 5–15 years) at presentation. The median duration of symptoms was 18 months (range 2–132 months). The median follow-up was 18.5 months (range 1–120 months). Seven (13.0%) boys had early urethral stricture at initial cystourethroscopy, and one (1.9%) developed stricture during follow-up. Thirty-six boys (66.7%) had previous circumcision and four (7.4%) had meatal stenosis. Eight (14.8%) had previous hypospadias repair. Conclusion: Whilst 50% of boys with IU do not require any specific treatment, those with severe/unremitting symptoms may benefit from a trial of urethral steroids or short-term urethral catheterisation. The mechanisms of benefit from these modalities are unclear and they require further evaluation.